Comparison of sonohysterography to hysterosalpingogram for tubal patency assessment in a multicenter fertility treatment trial among women with polycystic ovary syndrome - Christianson, Mindy S. (J Assist Reprod Genet, 2018)
PURPOSE: To compare saline infusion sonohysterography (SIS) versus hysterosalpingogram (HSG) for confirmation of tubal patency. METHODS: Secondary analysis of a randomized controlled trial, Pregnancy in Polycystic Ovary Syndrome II (PPCOS II). Seven hundred fifty infertile women (18–40 years old) with polycystic ovary syndrome (PCOS) were randomized to up to 5 cycles of letrozole or clomiphene citrate. Prior to enrollment, tubal patency was determined by HSG, the presence of free fluid in the pelvis on SIS, laparoscopy, or recent intrauterine pregnancy. Logistic regression was conducted in patients who ovulated with clinical pregnancy as the outcome and HSG or SIS as the key independent variable. RESULTS: Among women who ovulated, 414 (66.9%) had tubal patency confirmed by SIS and 187 (30.2%) had at least one tube patent on HSG. Multivariable analysis indicated that choice of HSG versus SIS did not have a significant relationship on likelihood of clinical pregnancy, after adjustment for treatment arm, BMI, duration of infertility, smoking, and education (OR 1.14, 95% CI 0.77, 1.67, P = 0.52). Ectopic pregnancy occurred more often in women who had tubal patency confirmed by HSG compared to SIS (2.8% versus 0.6%, P = 0.02). CONCLUSIONS: In this large cohort of women with PCOS, there was no significant difference in clinical pregnancy rate between women who had tubal patency confirmed by HSG versus SIS. SIS is an acceptable imaging modality for assessment of tubal patency in this population.